Studies in the History of the English Language. - Grund, Peter J.; Hartman, Megan (Topics in English linguistics ;, 2021)
The future of English linguistics as envisaged by the editors of Topics in English Linguistics lies in empirical studies which integrate work in English linguistics into general and theoretical linguistics on the one hand, and comparative linguistics on the other. The TiEL series features volumes that present interesting new data and analyses, and above all fresh approaches that contribute to the overall aim of the series, which is to further outstanding research in English linguistics.